Síntese de nanopartículas de fosfetos de metais de transição dispersas em carvões ativados e aplicação em processos Fenton - Goncalves, Gustavo dos Reis (2020)
Nanostructured materials based on transition metal phosphides have several interesting physical and chemical properties. Among them, we can mention the magnetic properties of this class of materials and their applications in heterogeneous catalysis. This